Answer:
- x + 3 = y ....... slope = -1 and y-intercept of 3
x - 3 = y ......... slope = 1 and y-intercept of -3
y = 3 x - 1 ......... slope = 3 and y-intercept of -1
y = 1 - 3 x ....... slope = -3 and y-intercept of 1
Explanation:
Just read the slope and y intercept from the equations since they are all given in slope-intercept form:
- x + 3 = y ....... slope = -1 and y-intercept of 3
x - 3 = y ......... slope = 1 and y-intercept of -3
y = 3 x - 1 ......... slope = 3 and y-intercept of -1
y = 1 - 3 x ....... slope = -3 and y-intercept of 1